The relationship between health literacy dimensions and perceived risk of cardiovascular disease in middle-aged Iranian women - Behnaz Enjezab; Fatemeh Zarehosseinabadi; Arefeh Dehghani Tafti; Mina Zarehosseinabadi (Wolters Kluwer Medknow Publications, 2021)
Background: The purpose of the study was to investigate the relationship between health literacy dimensions and the perceived risk of cardiovascular disease in middle-aged Iranian women. Materials and Methods: This is a descriptive-correlational study in which 280 women aged 40-60 years were investigated by random cluster sampling out of seven health centers in Yazd city in 2018. Data collection tools included predesigned demographic information from a standard Health Literacy for Iranian Adults (HELIA), and a standard perceived susceptibility and perceived risk components of the preventive behaviors of cardiovascular disease questionnaire. The data were analyzed using one-way ANOVA, independent t-test, Kruskal-Wallis, and Mann Whitney tests. Results: A significant relationship was identified between demographic information and health literacy (p < 0.001). The mean (SD) scores of the perceived risk of cardiovascular disease and health literacy appeared to be 30.71 (5.10) and 35.62 (15.32), respectively. The perceived risk of cardiovascular disease in the participants turned out to be significantly correlated with the accessibility dimension of health literacy (r = 0.31, p < 0.001), but it failed to have any significant relationship with demographic information, especially obesity. Conclusions: As there is a significant relationship between health literacy and perceived risk of cardiovascular disease, hence increasing the health literacy of middle-aged women, especially in persons with high body mass index through the media and health centers, considered as an important source of health information, can be an appropriate task to augment the perceived risk of cardiovascular diseases.